Preliminary Study of Phytoremediation for Sulphide Treatment using Scirpus grossus - Syarifah, Abd Rahim; Nor Azila, Ramli (Indian Society for Education and Environment, 2017)

(untitled)
Objectives: Phytoremediation is known as oneof the green solutions to remove toxic contaminants from waste using plants. In this phytoremediation study, the synthetic spent sulfidic caustic (SSC) was introduced to Scirpus grossus plant. The survival of the plant was observed physically and the percentage of sulphide removal from SSC was analyzed. Methods/Statistical Analysis: Methodology were comprised of initial growth of Scirpusgrossus, thegrowth of S. grossus after induced with synthetic SSC and preparation of synthetic SSC including analysis of pH, chemical oxygen demand (COD) and sulphide content. Findings: The physical observation on the plants showed that after five weeks of exposure, the withered leaves were detected in all sulphide concentration with the highest percentage recorded as 44.0% corresponded to the sulphide concentration of 4.24 mg/L. The analysis for sulphide concentration revealed the concentration of the sulphide reduced and meets the minimun concentration (<0.5 mg/L) as required in Standard A and B of Environmental Quality Act (Industrial Effluents) 2009.